Stem cell/cellular interventions in human spinal cord injury: Is it time to move from guidelines to regulations and legislations? Literature review and Spinal Cord Society position statement - (:unkn) unknown (SPRINGER, 2019)
Purpose In preclinical studies, many stem cell/cellular interventions demonstrated robust regeneration and/or repair in case of SCI and were considered a promising therapeutic candidate. However, data from clinical studies are not robust. Despite lack of substantial evidence for the efficacy of these interventions in spinal cord injury (SCI), many clinics around the world offer them as therapy. These clinics claim efficacy through patient testimonials and self-advertisement without any scientific evidence to validate their claims. Thus, SCS established a panel of experts to review published preclinical studies, clinical studies and current global guidelines/regulations on usage of cellular transplants and make recommendations for their clinical use. Methods The literature review and draft position statement was compiled and circulated among the panel and relevant suggestions incorporated to reach consensus. This was discussed and finalized in an open forum during the SCS Annual Meeting, ISSICON. Results Preclinical evidence suggests safety and clinical potency of cellular interventions after SCI. However, evidence from clinical studies consisted of mostly case reports or uncontrolled case series/studies. Data from animal studies cannot be generalized to human SCI with regard to toxicity prediction after auto/allograft transplantation. Conclusions Currently, cellular/stem cell transplantation for human SCI is experimental and needs to be tested through a valid clinical trial program. It is not ethical to provide unproven transplantation as therapy with commercial implications. To stop the malpractice of marketing such unproven therapies to a vulnerable population, it is crucial that all countries unite to form common, well-defined regulations/legislation on their use in SCI. Graphical abstract These slides can be retrieved from Electronic Supplementary Material. [GRAPHICS] .
Keywords: Guidelines; Spinal cord injury; Acute paraplegia; Clinical trial; Stem cell; Cellular interventions; Position statement; Regulations; OLFACTORY ENSHEATHING CELL; AUTOLOGOUS SCHWANN-CELL; CLINICAL-TRIALS; ICCP PANEL; AXONAL REGENERATION; PHASE-I; TRANSPLANTATION; THERAPY; CONDUCT; MARROW